Research Program on Type 1 Diabetes and Youth Depression in Puerto Rico (Revista Puertorriqueña de Psicologia, 2016)
This work reviews studies on Diabetes and youth depression in Puerto Rico. The first showed a depression rate of 45.5% among youth with Type 1 Diabetes (T1D).  Given its impact on T1D management, and the lack of interventions to target this link in an integrative way, the manual titled Cognitive-Behavioral Treatment for Depression in Adolescents with T1D was developed. We first used it in an Open Trial and currently assess the initial efficacy of its revised version to reduce depression and improve self-care, glycemic control and quality of life. We present its approach, and initial data on its feasibility, acceptability and potential to reduce emotional problems in T1D youth. We discuss implications of this line of research for health psychology, and its utility to model the development of interventions alike focused on other chronic illnesses.